1994
DOI: 10.1089/dna.1994.13.1117
|View full text |Cite
|
Sign up to set email alerts
|

The Surf-1 and Surf-2 Genes and Their Essential Bidirectional Promoter Elements Are Conserved Between Mouse and Human

Abstract: The organization of the Surfeit locus and the juxtaposition of at least five of the Surfeit genes (Surf-1 to -5) are conserved between mouse and human (Williams et al., 1988; Yon et al., 1993). In the mouse, the heterogeneous transcription start sites of the divergent Surf-1 and Surf-2 genes are separated by a maximum of only 73 bp (Williams and Fried, 1986). This region contains a bidirectional promoter composed of three major factor binding sites required for the efficient expression of both the Surf-1 and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 21 publications
1
28
0
Order By: Relevance
“…3 Similarly, it has been shown that park2 protein re-expression in hepatocellu- lar carcinoma cell lines does not produce an increase in the number of apoptotic cells, but leads to an increased sensitivity of cells to apoptosis induced by cell-cycle inhibitors, suggesting that PARK2 is involved in cell cycle regulation. 4 Only a few promoters with bidirectional functionality have been described [22][23][24] and typically demonstrate overlapping, but not identical expression patterns. Interestingly, PARK2 and PACRG have demonstrated a different tissue expression profile, 12 and while the function of PARK2 has been characterized, the role of PACRG remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…3 Similarly, it has been shown that park2 protein re-expression in hepatocellu- lar carcinoma cell lines does not produce an increase in the number of apoptotic cells, but leads to an increased sensitivity of cells to apoptosis induced by cell-cycle inhibitors, suggesting that PARK2 is involved in cell cycle regulation. 4 Only a few promoters with bidirectional functionality have been described [22][23][24] and typically demonstrate overlapping, but not identical expression patterns. Interestingly, PARK2 and PACRG have demonstrated a different tissue expression profile, 12 and while the function of PARK2 has been characterized, the role of PACRG remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Enzyme assays have revealed that the depression of mitochondrial respiration in this group of mutants cannot be explained in any simple way by the activities of different segments of the electron transport chain but rather appears to be related to inefficient transfer of electrons in the span between the bc 1 and cytochrome oxidase complexes. The mutations responsible for the respiratory defect have been localized to the yeast homolog of the SURF-1 gene, previously shown to be in a highly conserved gene cluster of several mammalian (10) and chicken genomes (11). We present evidence that the product of the yeast SHY1 gene is a membrane constituent of mitochondria and therefore is likely to function directly in some aspect of mitochondrial organization and function.…”
mentioning
confidence: 82%
“…DISCUSSION SURF-1 has been identified in mammalian (10), chicken (11), Drosophila melanogaster (31), and S. cerevisiae (GenBank, Z7297) genomes. Human, mouse, and chicken SURF-1 are part of a conserved locus that includes several other genes (10,11). The absence of this organizational feature in the fly and yeast genomes casts some doubt on its functional significance (27).…”
Section: Conferral Of Respiration By Partially Deleted Copies Of Shy1-mentioning
confidence: 99%
“…In fact, a considerable number of head-to-head pairs, for example, COL4A1/COL4A2 [13], DHFR/REP3 [10], SURF-1/ SURF-2 [11], E14/ATM [6], and TK/KF [12], have been found previously to be conserved among mammalian species. Since evolutionary conservation usually indicates functional importance, we proposed that the conservation of head-to-head gene organization has biological relevance to the function of the involved genes.…”
Section: The Conservation and The Biological Relevance Of Headto-headmentioning
confidence: 99%
“…Subsequently, SURF-1/SURF-2 [4], COL4A1/COL4A2 [1], RanBP1/Htf9-c [5], E14/ATM [6], BRCA1/NBR2 [7], DNA-PKcs/MCM4 [8], FEN1/C11orf10 [9], and so on were identified in human, hamster, rat, or mouse through individual experiments. Of them, many cases, such as DHFR/REP3 [10], SURF-1/SURF-2 [11], E14/ATM [6], and TK/ KF [12], were found to be conserved among mammalian species. Computational analysis revealed that more than 10% of human genes were organized in this head-to-head manner separated by less than 1,000 base pairs (bp), suggesting that bidirectional gene organization seems to be a common architectural feature of the human genome [2,9].…”
Section: Introductionmentioning
confidence: 99%